The influence of semi-actively controlled magnetorheological bogie yaw dampers on the guiding behaviour of a railway vehicle in an S-curve: Simulation and on-track test - Jeniš, Filip; Michálek, Tomáš; Kubík, Michal; Strecker, Zbyněk; Šlapák, Jiří; Mazůrek, Ivan (My University, 2024)
Many publications have shown that semi-actively controlled dampers could significantly improve the behaviour of a road or rail vehicle. In the case of a railway vehicle, these dampers promise to solve the contradiction between the damping requirements of different running modes (fast running on a straight track vs negotiating a tight curve). It is known that semiactive control of a bogie yaw damper can improve the vehicle behaviour when running fast on a straight track, but it is not known whether such semi-active control worsens the vehicle behaviour when negotiating a tight curve. This paper investigates the application of magnetorheological bogie yaw dampers in the locomotive bogie to reduce guiding forces and wear in wheel-rail contact when the vehicle negotiates the S-curve. The paper describes the magnetorheological damper, its mathematical model and the strategies for its semi-active control, followed by the results of simulations on a complex multibody locomotive model and on-track testing on a real vehicle. The simulations and on-track tests have shown that the use of semi-active control of the yaw dampers reduces the guiding force by about 10%. The reduction in these forces will lead to a reduction in wear in the wheel-rail contact.
Vliv semiaktivně řízených magnetoreologických tlumičů vrtivých pohybů podvozků na vodicí vlastnosti kolejového vozidla v S-oblouku: Simulace a jízdní zkouška
Keywords: semi-active; magnetorheological; yaw, damper; railway vehicle; S-curve; guiding force; wear; semiaktivní; magnetoreologický; vrtění; tlumič; kolejové vozidlo; S-oblouk; vodicí síla; opotřebení